Effects of internet-based training on antibiotic prescribing rates for acute respiratory-tract infections: a multinational, cluster, randomised, factorial, controlled trial. - Little, P; Stuart, B; Francis, N; Douglas, E; Tonkin-Crine, S; Anthierens, S; Cals, J; Melbye, H; Santer, M; Moore, M; Coenen, S; Butler, C; et al. (2013)
BACKGROUND: High-volume prescribing of antibiotics in primary care is a major driver of antibiotic resistance. Education of physicians and patients can lower prescribing levels, but it frequently relies on highly trained staff. We assessed whether internet-based training methods could alter prescribing practices in multiple health-care systems. METHODS: After a baseline audit in October to December, 2010, primary-care practices in six European countries were cluster randomised to usual care, training in the use of a C-reactive protein (CRP) test at point of care, in enhanced communication skills, or in both CRP and enhanced communication. Patients were recruited from February to May, 2011. This trial is registered, number ISRCTN99871214. RESULTS: The baseline audit, done in 259 practices, provided data for 6771 patients with lower-respiratory-tract infections (3742 [55·3%]) and upper-respiratory-tract infections (1416 [20·9%]), of whom 5355 (79·1%) were prescribed antibiotics. After randomisation, 246 practices were included and 4264 patients were recruited. The antibiotic prescribing rate was lower with CRP training than without (33% vs 48%, adjusted risk ratio 0·54, 95% CI 0·42-0·69) and with enhanced-communication training than without (36% vs 45%, 0·69, 0·54-0·87). The combined intervention was associated with the greatest reduction in prescribing rate (CRP risk ratio 0·53, 95% CI 0·36-0·74, p<0·0001; enhanced communication 0·68, 0·50-0·89, p=0·003; combined 0·38, 0·25-0·55, p<0·0001). INTERPRETATION: Internet training achieved important reductions in antibiotic prescribing for respiratory-tract infections across language and cultural boundaries. FUNDING: European Commission Framework Programme 6, National Institute for Health Research, Research Foundation Flanders.